Patient-derived pancreatic tumour organoids identify therapeutic responses to oncolytic adenoviruses - Giulia Raimondi; Ana Mato-Berciano; Silvia Pascual-Sabater; Maria Rovira-Rigau; Miriam Cuatrecasas; Constantino Fondevila; Santiago Sánchez-Cabús; Harry Begthel; Sylvia F. Boj; Hans Clevers; Cristina Fillat (EBioMedicine, 2020)
Background: Pancreatic patient–derived organoids (PDOs) are a well-established model for studying pancreatic ductal adenocarcinoma (PDAC) carcinogenesis and are potential predictors of clinical responses to chemotherapy. Oncolytic virotherapy is envisioned as a novel treatment modality for pancreatic cancer, and candidate viruses are being tested in clinical trials. Here, we explore the feasibility of using PDOs as a screening platform for the oncolytic adenovirus (OA) response. Methods: Organoids were established from healthy pancreas and PDAC tissues and assessed for infectivity, oncoselectivity, and patient-dependent sensitivity to OA. Antitumour effects were studied in vivo in organoid xenografts. Further evaluation of oncolytic responses was conducted in organoids derived from orthotopic models or metastastic tissues. Findings: Oncolytic adenoviruses display good selectivity, with replication only in organoids derived from PDAC tumours. Furthermore, responses of PDOs to a set of OAs reveal individual differences in cytotoxicity as well as in synergism with standard chemotherapy. Adenoviral cytotoxicity in PDOs is predictive of antitumour efficacy in a subcutaneous xenograft setting. Organoids from orthotopic tumours and metastases in nude mice mirror the viral preference of PDOs, indicating that PDO sensitivity to OAs could be informative about responses in both primary tumours and metastatic foci. Interpretation: Our data imply that pancreatic PDOs can serve as predictive tools for screening for sensitivity to OA.